課程知識觀的當代重構：困境與出路Contemporary Reconstruction of the View of Curriculum Knowledge: Difficult Position and Outlet - 李召存 Zhao-cun Li (Higher Education Foundation, 2009)
課程知識問題是學校教育永遠也無法繞開的一個基本的核心話題。二十一世紀初以來，隨著新課程改革深入推進，在中國教育領域展開的課程知識大討論，已導致了人們的課程知識觀認同危機。考察近幾年的相關研究，在方法論上體現為一種「外推式」，而非「內生式」研究。為此，當代課程知識觀的重構需要從兩條進路展開：即從課程與教學理論和實踐歷史發展的內部，去梳理課程知識觀發展演變的內在理路；以課程知識與教學活動中，兒童之間的現實關係為切入點，去考察課程知識觀重構的現實基礎。 The issue of curriculum knowledge is a basic topic which school education may not slide over for ever. The widely controversy in the field of education in china has lead to the crisis of identity about the view of curriculum knowledge from the beginning of 21 century, with the further development of New Curriculum Reform. We find the many researches about curriculum knowledge are not generated from the inner educational field, but inspired by related studies outside. Therefore, we argue the recontruction of the view of curriculum knowledge must be done from two approaches: heckleing the inner logic of the evolvement about the view of curriculum knowledge, and examinating the practical base of reconstruction of the curriculum knowledge view from the perspective of real relationship between curriculum knowledge and children.